China's Role in the Rising of the South: Vision for 2030. (15th July 2014) - Hu, Angang; Gao, Yuning; Yan, Yilong; Wei, Xing
Abstract This article examines China's major development contributions, looking at its wider impact on world development. In particular, the article examines the impact of China's development on the changing pattern between the North and South and the human development index. The factors and related regimes behind these phenomena are discussed and a conceptual model is constructed, providing a meta‐analysis of the evolution of China's role, based on the structural interpretation of external impetus and barriers, as well as internal advantages and shortcomings. The authors' long‐term projections show that the rise of the South, led by China, will be the most important shift in the world's landscape with respect to the development of the emerging world, perhaps leading other large developing economies to play a more prominent role in international development in the future, bringing common development, common prosperity and common progress to the world.